Nanotechnology in Herbal Medicine: A Promising Approach for Enhanced Drug Delivery and Therapeutic Efficacy - Tajne, Prachi S.; Kalamb, Vaishnavi S.; Girhe, Pavan N.; Bakal , Ravindra L.; Hatwar , Pooja R. (Journal of Drug Delivery and Therapeutics, 2025)
Nanotechnology has revolutionized the field of herbal medicine by providing a platform for enhanced drug delivery and therapeutic efficacy. The use of nanocarriers and nano formulations has improved the bioavailability and solubility of herbal extracts, allowing for targeted and controlled release of active compounds. This review highlights the potential of nanotechnology in herbal medicine, including the types of nano formulations, methods of preparation, and applications in various diseases. The advantages of nano formulations, such as improved pharmacokinetics and pharmacodynamics are also discussed. Furthermore, the role of computational tools and artificial intelligence in nanotechnology is explored, including their potential to transform drug delivery and disease monitoring. Despite the promising benefits, the drawbacks of nanotechnology, including biocompatibility and toxicity concerns, are also addressed. Overall, nanotechnology has the potential to enhance the therapeutic efficacy and safety of herbal medicines Keywords: Nanotechnology, Herbal medicine, Nano formulations, Artificial intelligence, Drug delivery